Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fenvs.2022.878394
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Consumption and Economic Growth Nexus—A Systematic Literature Review

Abstract: An efficient use of energy is the pre-condition for economic development. But excessive use of fossil fuel harms the environment. As renewable energy emits no or low greenhouse gases, more countries are trying to increase the use of energies from renewable sources. At the same time, no matter developed or developing, nations have to maintain economic growth. By collecting SCI/SSCI indexed peer-reviewed journal articles, this article systematically reviews the consumption nexus of renewable energy and economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 55 publications
1
35
0
1
Order By: Relevance
“…They concluded that RE positively affects economic growth in OECD countries, but it has no significant effect on developed countries. A similarly ambiguous outcome can be found in numerous empirical studies that analyze the relationship between RE and economic growth [10].…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…They concluded that RE positively affects economic growth in OECD countries, but it has no significant effect on developed countries. A similarly ambiguous outcome can be found in numerous empirical studies that analyze the relationship between RE and economic growth [10].…”
Section: Literature Reviewmentioning
confidence: 88%
“…The latter is sometimes referred to as research on the renewable energy vs. economic development nexus, and it is the main focus of this study. Analyses of the topic have been performed at various levels of aggregation (firm, industry, country), and they have earned some significant attention in recent years [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The need to produce enough energy to meet the world's increasing energy demand has become more necessary in recent years due to factors such as growing population, industrialization, and changing living conditions as a result of economic development. The world currently generates its energy mainly from non-renewables, which has negative implications for the environment as a result of the release of greenhouse gases (GHG) [1][2][3][4]. Hence, introducing an alternative source of energy generation becomes more pertinent.…”
Section: Introductionmentioning
confidence: 99%
“…A thriving global economy requires energy (Bhuiyan et al, 2022;Xie et al, 2022). In other words, all sectors directly or indirectly linked to economic growth and development necessitate using some form of energy.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Energy demand has increased in both developed and developing countries in recent decades. While developed countries' living standards have broadly improved, developing countries have lagged in matching energy supply with energy demand due to increasing living standards, population, urbanization, and industrialization (Bhattarai et al, 2022;Bhuiyan et al, 2022). In 2020, the total global primary energy consumption (PEC) was 557 Exajoules (EJ) (BP, 2021).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%